Correlation between Body Mass Index and abdominal circumference in Belgian adults: a cross-sectional study - Wilmet Gaëlle; Verlinde Rolf; Vandevoorde Jan; Carnol Laure; Devroey Dirk (Sciendo, 2017)
Introduction. Traditionally, the body mass index (BMI) is used to describe anthropometric measurements and to assess weight-related health risks. However, the abdominal circumference (AC) might also be a valuable parameter to estimate this risk. This study aims to describe an association between the BMI and the AC.